Parents’ Perception regarding Nursing Care of their Child in Tertiary Care Hospital, Lahore - Naila Maqbool, Hasnain Ahmad Raza , Imran Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The nursing care of child effect the health of the child somehow. As, the health of child is effecting the health of the parents. This research was planned to check the perception of parents related to nursing care of their admitted child in the hospitals. Materials and Methods: This study was a crossectional and conducted at Sir Ganga Ram Hospital, Lahore from Septmeber 2021 to January 2022. After getting approval and review from hospital committee, a total of 120 parent were selected for data collection out of which 100 filled out structured questionnaires. Data was analysed on SPSS version 21.0, and different tables were generated. Results: The average age of parents was 31.19 years, while about 45% of them have some bachelor level education. The level of good perception was maximum in parents having higher eduation while bad perception was in having secondary education. Overall perception rates of good and bad perception was 63% and 37%, respectively. Conclusion: The majority of the parents have a good perception of nursing care of their ill child. More than one-third of the participants agreed that nurses should not be rude, hostile, and unkempt. Nurses’ managers should support the nurses to get a higher level of education and to get admissions in specialization so the number of specifically skilled holders should be increased in the specific ward. Keywords: Perception, Parents, Nursing care